Subjective assessment of sensory function and oral function decline in older adults. - Tetsuo Ichikawa; Tomoya Koda; Mio Kitamura; Takahiro Kishimoto; Takashi Matsuda; Takaharu Goto; Masayuki Domichi; Akiko Suganuma; Shinji Fujiwara; Yasuhiko Shirayama; Kazuhiko Kotani; Naoki Sakane (PLoS ONE, 2025)
Sensory decline in older adults significantly affects quality of life and contributes to cognitive decline, depression, falls, and injuries. Although several studies exist in this area, most were focused on individual senses, with few being conducted on comprehensive assessments of all five senses. The aim of this study was to investigate the relationship between subjective sensory assessment and oral function, to developing health strategies. This study was conducted as part of the Mima-SONGS Study for examining relationships between oral, cognitive, and physical functions, social factors, nutrition, and health, in older adults living in a mountainous region of Japan. The cohort included 62 participants (40 women and 22 men; mean age: 80.8 yrs.) as of December 2023. Participants completed a questionnaire assessing sensory perception and eating enjoyment rated on a four-point scale. Oral health was evaluated based on the conditions of remaining teeth, tongue coating, oral dryness, occlusal force, oral diadochokinesis, and repetitive salivary swallow test. Sensory assessments indicated minimal overall issues, with auditory problems scoring the highest and taste/tactile issues scoring the lowest. Males scored higher in hearing and maximum occlusal force. Eating enjoyment was generally high and negatively correlated with olfactory and taste problems. Subjective sensory issues were less strongly associated with oral function and age. Most older adults were not subjectively aware of sensory problems, especially olfaction, taste, and tactile problems. Subjective sensory problems showed a moderate but meaningful association with oral health conditions and age. The findings might be valuable data developing future support measures.